The Gender Factors in the Differences in the Impact of Islamophobia in The Novels The Girl in the Tangerine Scarf (2006) and Once in a Promised Land (2007) - Filza Rayda (Lakon : Jurnal Kajian Sastra dan Budaya, 2026)
This study discusses how gender factors greatly influence the differences in experiences of Islamophobia experienced by female and male characters in the novels The Girl in the Tangerine Scarf (2006) by Mohja Kahf and Once in a Promised Land (2007) by Laila Halaby. Both novels raise issues of Islamophobia experienced by Muslims, making them representative of Muslims who experience Islamophobia, especially after the events of 9/11. This study uses intersectionality theory, gender-based Islamophobia, and gender performance. This study uses close-reading techniques to analyze the differences in the treatment of Islamophobia caused by the gender of the characters, Khadra and Salwa (female) and Jassim (male).